1979
DOI: 10.1007/bf00346673
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fecundity of Drosophila melanogaster and D. simulans in response to selection for competitive ability

Abstract: 1. Equal numbers of the sibling species Drosophila melanogaster and D. simulans were allowed to compete in population cages. Two sets of 5 cages each-A & B-took 20 and 26 weeks respectively until D. simulans comprised less than 15% of the population for 2 successive generations. 2. At the beginning of each cage set, the fecundity of stock females of each species in the presence of con-& heterospecific females, con- and heterospecific larvae, distilled water and a water soluble extract from larvainfested media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Larval biotic residues are known to inhibit larval survivorship, female fecundity and adult size (Budnic & Brncic 1974, 1976Aiken & Gibo 1979;Botella et al 1983Botella et al , 1985Joshi et al 1996). Larval biotic residues are known to inhibit larval survivorship, female fecundity and adult size (Budnic & Brncic 1974, 1976Aiken & Gibo 1979;Botella et al 1983Botella et al , 1985Joshi et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Larval biotic residues are known to inhibit larval survivorship, female fecundity and adult size (Budnic & Brncic 1974, 1976Aiken & Gibo 1979;Botella et al 1983Botella et al , 1985Joshi et al 1996). Larval biotic residues are known to inhibit larval survivorship, female fecundity and adult size (Budnic & Brncic 1974, 1976Aiken & Gibo 1979;Botella et al 1983Botella et al , 1985Joshi et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The fecundity and longevity of D. simulans females decreases as the relative frequency of D. melanogaster to D. simulans increases, but the fecundity of D. melanogaster does not change (Moth 1974;Moth and Barker 1977). It has been consistently observed that D. melanogaster strongly excludes D. simulans (Moore 1952;Barker 1963Barker , 1971Aiken and Gibo 1979;Hedrick 1972). This asymmetric reproductive interference should have been caused by differences in the ability of males to discriminate between conspecific and heterospecific females, because female receptivity does not differ between the two species (Manning 1959).…”
Section: Drosophilamentioning
confidence: 99%
“…Rose & L. D. Mueller, unpublished data). In studies of interspecific competition between Drosophila species, the inhibitory effects of larval biotic residues on both larval viability (Budnick & Brncic, 1974, 1976 and female fecundity (Aiken & Gibo, 1979) were observed. Subsequently, exposure to urea was shown to result in the slower development and reduced survivorship of D. melanogaster larvae (Botella et a!., 1983(Botella et a!., , 1985.…”
Section: Introductionmentioning
confidence: 99%